Effectuation to Cognize malignancy risk and accuracy of fine needle aspiration cytology in salivary gland using "Milan System for Reporting Salivary Gland Cytopathology": A 2 years retrospective study in academic institution - Veer Karuna; Priya Gupta; Monika Rathi; Kriti Grover; Jitendra Singh Nigam; Nidhi Verma (Wolters Kluwer Medknow Publications, 2019)
Background: To accost things in a particular disciple, egress related to Fine Needle Aspiration Cytology (FNAC) and to standardize reporting pattern, a framework "Milan System for Reporting Salivary Gland Cytopathology" (MSRSGC) has been sponsored. Aim: Aim of this study was to evaluate the potency of salivary gland FNAC reported under Milan guidelines, to calculate malignancy risk, and to compare the preoperative cytological diagnoses with the postoperative histopathological diagnoses. Settings and Design: This was a retrospective study over a period of 2 years (May 2016 to April 2018), which was classified according to Milan system and correlation with histopathology. Furthermore, the risk of malignancy was calculated for all the diagnostic categories. Materials and Methods: FNAC were analyzed on 105 patients with palpable salivary gland. Results were distributed into six categories. About 76 cases were surgically treated and resected tissues were submitted for histopathological examination. Statistical Analysis: The various diagnostic values of the procedure were calculated using the standard formula. Results: We reviewed 105 salivary gland FNA samples and recorded interpretations according to the proposed standardized six categories. Among them, category IV (neoplastic) had more cases (57.14%). The rates of malignancy in histology were as follows: (1) nondiagnostic, 0.0%; (2) nonneoplastic, 0.0%; (3) atypia of undermined significance, 50.00%; (4a) benign, 02.44%; (4b) uncertain malignant potential, 33.33%; (5) suspicious for malignancy, 100%; and (6) malignancy, 93.33%. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of Milan system came out to be 85.00%, 98.14%, 94.44%, 94.64%, and 94.59%, respectively. Conclusion: The six-tier diagnostic categories of the Milan system helps in triaging patients with salivary gland swelling and thus facilitate individualized management.